2016
DOI: 10.1016/j.neurobiolaging.2016.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation during rehabilitative training enhances recovery of forelimb function after ischemic stroke in aged rats

Abstract: Advanced age is associated with a higher incidence of stroke and worse functional outcomes. Vagus nerve stimulation (VNS) paired with rehabilitative training has emerged as a potential method to improve recovery after brain injury but to date has only been evaluated in young rats. Here, we evaluated whether VNS paired with rehabilitative training would improve recovery of forelimb function after ischemic lesion of the motor cortex in rats 18 months of age. Rats were trained to perform the isometric pull task, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 39 publications
4
55
0
Order By: Relevance
“…Preclinical studies demonstrate that VNS paired with rehabilitative training improves recovery in models of tinnitus, ischemic and hemorrhagic stroke, and traumatic brain injury (Engineer et al, 2011, Khodaparast et al, 2013, Khodaparast et al, 2014, Hays et al, 2014, Pruitt et al, 2016, Khodaparast et al, 2016, Hays et al, 2016). Moreover, clinical studies provide an initial indication of the clinical utility of VNS-based plasticity therapies for tinnitus and stroke patients (Dawson et al, 2016, De Ridder et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies demonstrate that VNS paired with rehabilitative training improves recovery in models of tinnitus, ischemic and hemorrhagic stroke, and traumatic brain injury (Engineer et al, 2011, Khodaparast et al, 2013, Khodaparast et al, 2014, Hays et al, 2014, Pruitt et al, 2016, Khodaparast et al, 2016, Hays et al, 2016). Moreover, clinical studies provide an initial indication of the clinical utility of VNS-based plasticity therapies for tinnitus and stroke patients (Dawson et al, 2016, De Ridder et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Body temperature was maintained throughout surgery and neural recording using a feedback-controlled electric warming pad (FHC, Bowdoin, ME). Subjects were implanted with a custom made platinum-iridium bipolar stimulating cuff electrode on the left cervical vagus nerve, as previously described (Engineer et al, 2011, Khodaparast et al, 2013, Khodaparast et al, 2014, Hays et al, 2014, Pruitt et al, 2016, Khodaparast et al, 2016, Hays et al, 2016, Hulsey et al, 2016). A transient drop in blood oxygen saturation in response to a short (~3 sec) VNS train was used to confirm that the cuff electrode was functional.…”
Section: Methodsmentioning
confidence: 99%
“…32,33 In this light, an increasing number of studies have shown that TNS is beneficial for seizure control, depression, and migraine, and, very recently, the FDA approved a clinical trial for TNS treatment of Lennox-Gastaut syndrome. 34 In addition to epilepsy and depression, researchers have proposed a clinical application for VNS and TNS for treating variety of disorders, such as migraine, 35 anxiety, 36 cognitive impairment, 37,38 Alzheimer's disease, 39 autism, 40 tinnitus, 41,42 poststroke symptoms, [43][44][45] post-traumatic stress disorder, 46 eating disorders 47 and obesity. 48 Although clinical trials on the topic are accumulating, most of them are preliminary proof-ofconcept pilot studies obtained with limited sample sizes.…”
Section: Clinical Applications Of Vagus-and Trigeminal-nerve Stimulatmentioning
confidence: 99%
“…Previous studies have demonstrated that VNS during rehabilitative training improves recovery of motor function in several models of brain injury (Khodaparast et al, 2016, 2014; Hays et al, 2014a,b, 2016; Meyers et al, 2018; Morrison et al, 2019). The therapeutic effects of pairing VNS with motor rehabilitation persist even after the cessation of stimulation, suggesting that the VNS-induced plasticity and learning are long-term (Khodaparast et al, 2014; Hays et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%